Uncertainty of the implementation time of geodynamic monitoring system in multi-criteria ranking of alternatives - O.R. Kuzichkin; I.V. Loginov; V.T. Eremenko; S. V. Eremenko; G.S. Vasilyev; A.V. Grecheneva (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The paper deals with the problem of ranking alternatives to geodynamic monitoring systems in the case of uncertainty of their implementation time. The problem is characterized by the fact that the choice of alternatives and the effect of it depends on the quality properties of the applied organizational and technical solutions, taking into account the time of implementation. The ordering of alternatives is proposed taking into account the uncertainty of the implementation time factors. Ranking is realized by comparing the trees of functional characteristics of alternatives taking into account the compliance of their characteristics with time-varying requirements. The scope of the proposed method is the choice of configurations of geodynamic monitoring systems with significant differences in the implementation time of alternatives.